Neue Perspektiven auf die Sparkassen der DDR: Ein Überblick über Quellenbestände und Forschungsfelder - Gunnar Take (IBF - Institut für Bank- und Finanzgeschichte e.V., 2025)
– The purpose of this paper is to revive the historical research on the GDR's savings banks. It argues that socialist banks were interesting intermediary organizations which have so far been largely overlooked by financial, economic, and social historians. Hence, sources produced by the socialist banking apparatus have not received enough attention in comparison to their potential. The main part comprises six chapters which give extensive suggestions about topics worthy of future research regarding 1) personnel and organization of savings banks, 2) their role as part of the dictatorial regime, 3) saving and hoarding, 4) lending, 5) international contacts and comparisons, and 6) deviant behavior and self-portrayals. These ideas include the contributions of savings banks towards socialist state building and crisis management, the temporary existence of anonymous accounts in an apparent contradiction to Socialist propaganda, the use of lending as an instrument to influence consumption patterns and many more. In each case, an outline of the relevant state of research is given and archive collections or published sources are recommended. Part III contains a survey of German archives from the federal to the local level which contain relevant source material, particularly the historical archives of the East German savings banks and of their association.
Keywords: E21; G21; N24; P21; P34; 330; Bank History; History of Financial Institutions; Socialism; Savings Banks; GDR; Archives; Sources